STUDY OF HYBRID ELECTRICAL SYSTEM PLANNING IN THE RESEARCH AND COMMUNITY SERVICE INSTITUTE BUILDING - Muzakkir, Chaerul; Fitriah, Fitriah; Arsyad, M. Iqbal (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2023)
This research plans a hybrid system in the LPPKM Untan building, comparing the energy and economic aspects of PLN and PLTS using monocrystal type solar panels with a capacity of 320 Wp, and finding the total needs and capacity of solar panels, batteries, SCC, inverters, and ATS. In the LPPKM building with an installed electrical power capacity of 23 kVA with a hybrid system will compare PLN and PLTS energy by 50% and 30% of the maximum daily power of 11.5 kW. Energy and economic analysis found that the most efficient PLTS energy cost to use, meeting and even exceeding the daily and monthly use of electric power in the LPPKM building is PLTS with a capacity of 50% (10,857.28 kWp / year) with cost savings of Rp. 15,486,877 kWp / year with a very high LCC value compared to using a capacity of 30% of the maximum power even though the LCC is low. The feasibility of investment made by the 50% capacity PLTS shows an NPV value of Rp. 28,394,341, -. PI = 1.16 and DPP value of 17 years. Indicating that the construction of PLTS in LPPKM is feasible by using a PLTS capacity of 50%.